ISOLATION AND IDENTIFICATION OF STIGMASTEROL FROM ASCLEPIAS CURASSAVICA AND EVALUATION OF ANTI-INFLAMMATORY ACTIVITY - SAHAYA MARY,; MK MAHESH,; KAVISHANKAR GAWLI, (International Journal of Pharma and Bio Sciences, 2015)
Asclepias curassavica is a milk weed plant known for its medicinal properties.The present investigation was carried out to evaluate the anti-inflammatory potential of chloroform fraction of A. curassavica in modulating the inflammatory effect in carrageenan-induced mice. The effect of sub-fraction 2 obtained from chloroform extract was tested for the above model with varying dose. The reduction in the paw edema was measured using plethysmometer for the duration of 1-4 h. The MTT analysis was carried out to study the toxicity using SH-SY5Y cells and cell viability was checked. The anti-inflammatory activity was expressed as the mean increase in paw volume in terms of mL and percentage inhibition in paw volume. The sub-fraction 2 of chloroform extract of A. curassavica at 45 and 180 mg/kg.b.w dose significantly reduced (p ≤ 0.01) paw edema when compared with control. Further, characterization of sub-fraction 2 using LCMS, NMR and IR revealed the presence of Stigmasterol, which is known to possess anti-inflammatory and other beneficial effects. In conclusion, the plant A. curassavica may be useful in treating inflammatory responses associated with different disorders.